Representation of Amoral Values in Hikayatu Buhlul Short Story by Kamil Kaelani as a Media for Children’s Character Building - Ananta, Maghfiroh Fitri; Zawawi, Moh; Moh Zawawi, Moh Zawawi (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2025)
In the contemporary digital era, the cultivation of children's character encounters substantial challenges, particularly in the context of the erosion of moral and cultural values within society. Moreover, the escalation in youth violence signifies that character education has not been effective in cultivating a noble younger generation. The present study has two objectives. Firstly, it seeks to provide a representation of immoral values in the short story Hikayat Buhlul by Kamel Kilani. Secondly, it will sanalyse these values in shaping the moral knowledge, moral feelings and moral actions of the main characters. This analysis will be based on Thomas Lickona's character education theory. The present study employs a qualitative descriptive method, with primary data derived from the short story Hikayat Buhlul and secondary data from journals, articles, and relevant literature. The data collection techniques employed in this study encompass the reading and note-taking methods. The subsequent data analysis is guided by the Miles and Huberman model, which involves data reduction, data presentation, and conclusion drawing. The results of the study indicate that there are four data related to moral knowledge, five data for moral feelings, and five data for moral actions. The present study concludes that children's literature plays a crucial role in shaping children's character through implicit moral messages, with the family environment, especially the role of parents, as the main factor in the internalisation of moral values.